Increasing Member Performance through Transformational Leadership, Organizational Culture, and Human Capital - Henri Ahmad Badawi; M. Ch. Sina Setyadi; Boge Triatmanto (Trescode Green Organization, 2024)
This research aims to analyze the influence of transformational Leadership, organizational Culture, and human capital on the individual performance of members of the Soewondo Air Force Base Medan, both simultaneously, partially, and dominantly. The type of research used is explanatory research. This research was conducted at Soewondo Air Force Base Medan at the address Jl. Imam Bonjol No.1, Suka Damai, Kec. Medan Polonia, Medan City, North Sumatra 20212. The research population and sample were all members of the first officers of the Soewondo Air Force Base Medan, namely 95 members. Since the population is small, census research is used; all Soewondo Medan's first officers will be research respondents. The analysis method uses multiple linear regression and hypothesis testing. The research results show that transformational Leadership, organizational Culture, and human capital affect individual performance among members of the Soewondo Air Force Base Medan base, both simultaneously and partially. Furthermore, this research identifies that human capital has a dominant influence on the performance of Soewondo Air Force Base Medan members. Leaders should pay more attention to organizational Culture to improve performance by encouraging members to innovate and work to be results-oriented.